Dietary Intake of Macronutrient and Basic Metabolic Index (BMI) of Women in Rural Pakistan (P04-178-19). (13th June 2019) - Israr, Muhammad
Abstract: Objectives: To investigate the nutritional status and macronutrients intake of women in rural area of Pakistan. Methods: The 24-hour Memory Recall Questionnaire Method and Duplicate Food Sample Procedure were used. Information was collected from 150 women using questionnaire and intake of macronutrients were calculated using the excel spread sheet. Randomly 30 women were selected for Duplicate Food Sample Procedure and samples were collected, dried, preserved and were subjected to biochemical analysis for proximate composition. Results: 24hr Memory Recall Questionnaire Method. The food intakes were 814 g/women/day and energy intake was 2164 kcal/women/day which was adequate and according to the recommendations. The protein consumption was 56 g/woman/day which was not much higher than the RDA. The consumption of fat was 85 g/women/day. The carbohydrates, fiber and ash intakes were 314, 6.9 and 10.18 g/woman/day respectively. Duplicate Food Sample Method The macronutrient intake was generally adequate. The protein consumption was 52 g/woman/day which was not significantly higher. Fat Consumption was 25 g/woman/day which was significantly higher than the RDA. The protein corresponded to 11–12% of the total energy, fat corresponded to 8–10% of the total energy intakes. The carbohydrates and ash intakes were 190 g and 7 g/women/day respectively. Anthropometry The BMI ranged from 19.6 to 52.2 with a mean of 28.54. All women have BMI greater than 18.5 and none of them were identified as being underweight; 30% were normal; 35.3% were overweight; while 34.7% were obese. The mean weight was 65.32 kg which ranged from 41 kg to 81 kg while the mean height was 1.52 m ranging from 1.14 m to 1.72 m. Conclusions: The discussions in the preceding sections of this manuscript provide basis for the conclusion of this study. Nutritional status of women revealed that quite a large proportion of the women were overweight and obese. The women's energy intakes were marginally adequate as it was almost equal to the recommendations. The mean protein intakes of women were suitable in contrast with the protected stage intakes. Average fat intake of the women was according to the recommendations. Funding Sources: The study was conducted on self finance bases.